The Phenomenon of Fast Fashion on Environmental Pollution from The Perspective of Al-Qur'an - Romziana , Luthviyah; Nabila, Izzah Nurin; Salomon , Noah (LPPPM STAI Darul Hikmah Bangkalan, 2024)
The fast fashion phenomenon has become the second most controversial pollution industry in the world after the petroleum industry. Researchers want to instill the values of religiosity and environmental balance to answer the phenomenon of fast fashion and its impact in the Qur'an. The research method used is qualitative research with a type of literature through an analytical descriptive approach and maudhu'i method, through two data sources, namely primary sources in the form of the Qur'an, and secondary sources derived from several studies of tafsir books, journals, and scientific videos about this phenomenon. The researcher concludes that the phenomenon of fast fashion according to the Qur'an is included in unjust behavior that can de-stabilize the earth (Hud verse 116). This phenomenon arises because of the excessive attitude of humans in obeying their lust for fashion (Al-A'raf verse 31 and Al-Mu'minun verse 71). Basically, humans have been given the mind to think about cause and effect (Al-Jatsiyah verse 13). Because, the impact of the fast fashion phenomenon on environmental pollution according to the Qur'an includes the cause of destruction on earth (Yunus 40), pollution of land and sea (Ar-Rum verse 41), irregular industry that makes the environment a mess (Al-Baqarah verse 205), and includes deviant and useless actions (Al-A'raf verse 56).